Pengembangan Film Pembelajaran Sosiologi Pada Kompetensi Mendeskripsikan Nilai dan Norma Yang Berlaku Dalam Masyarakat Untuk Siswa Kelas X Di SMA Negeri 2 Singaraja - I Made Leo Suandinatha; I Ketut Resika Arthana; I Made Agus Wirawan (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2015)
Sociology Learning Film in competency to describe value and norm which are applicable in Society for ten grade class of SMA Negeri 2 Singaraja. It was made based circumstances of the students less. It was known through interviews between sociology’s teachers at SMAN 2 Singaraja and the researcher. This film is a medium that will be used to support the teaching and learning process in the classroom. The film showed several scenes base on the indicators of material on values and norms. However, the violation scene of values and norms is more dominant in this movie. In Making the Sociology Learning Film, the researcher used ADDIE development model. ADDIE development model was a model that was grounded in instructional design approach that was effective and efficient systems as well as an interactive process that was the result of the evaluation of each phase can bring development to the next phase of learning. The end result is a product of an initial phase for the next phase. ADDIE Model consists of five parts, namely: 1) Analyze (Analysis), 2) Design (Design), 3) Develop (Development), 4) Implement (Implementation), 5) Evaluate (Evaluation). After conducted an assessment using a questionnaire, the sociology of learning this movie got a positive response. The results of the test of expert sociological learning film material got the percentage of 95.4%, from one media expert gained 91.1%, a gain of 95.6% 2 media, media experts and 3 receive 80% of students gained 91% response. So that the average of 91.6% obtained with the title very well and did not need to be revised description. The final result of this sociology learning film was DVD. Sociology learning film is expected to help the learning process in the classroom. In addition, the film has become a guide sociological of study for educators in order to think of a unique medium that makes supporting in learning in the classroom. So the learning objectives can be achieved.